The loving relationships of young users from Manaus city of the dating app Tinder (Research, Society and Development, 2021)
Social networks and applications on the market have been offering greater proximity and ease of communication between people. In 2013, a tool for love relationships emerged in Brazil which managed to connect people from all over the world, becoming very popular, especially among young people. These virtual relationships have very unique characteristics, which arouse emotional and social issues both for those who live in the relationship and for the observers. To debate the subject, the objective of this research was to understand what leads young people from Manaus to have romantic relationships through the dating app Tinder. This investigation had a quantitative-qualitative, descriptive and field approach. As a research instrument, a questionnaire with open and closed questions was used, applied through Google Forms to 30 young people aged 18 to 24 years. As a result, it was found that young people have a tendency to use this tool, as it allows for easier communication, and also allows meeting people with common tastes. Furthermore, it was identified that the majority of Tinder users are individuals who describe themselves as extroverts, and who cannot maintain lasting relationships outside the virtual context, due to insecurity and the idea of ​​a perfect relationship. The results show that conversations between Tinder users usually last a few months, being limited only to virtual relationships.